2013
DOI: 10.5114/pjp.2013.39335
|View full text |Cite
|
Sign up to set email alerts
|

Association of loss of heterozygosity with shorter survival in primary glioblastoma patients

Abstract: Loss of heterozygosity (LOH) co-deletion 1p/19q, MGMT promoter methylation and/or IDH1 mutation generally signify a better prognosis for patients with glioma. However, the influence of 1p/19q co-deletion and the LOH on other chromosomes in primary glioblastoma on survival is still debatable. The aim of our study was to identify LOH on chromosomes 1p, 19q, 9p, 10q, 13q, and 17p, and evaluate their impact either alone or 1p/19q co-deletion or by groups of LOH on the overall survival of 42 primary glioblastoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
(80 reference statements)
2
12
0
Order By: Relevance
“…The significance of differences in the frequencies of molecular events in the chromosome region 10q23. 3 17 Our experience with the original protocol demonstrated that endogenous control system included loci whose copy numbers are frequently altered in glioblastoma according to our observations (not shown) and previously published data. 4,19 We developed an original endogenous control system and designed specific primer pairs (Supporting Information Table 2) based on the GRCh37/hg19 genome assembly with comprehensive annotations and the data accumulated in the past decade for alterations in copy numbers of genomic regions in glioblastoma.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The significance of differences in the frequencies of molecular events in the chromosome region 10q23. 3 17 Our experience with the original protocol demonstrated that endogenous control system included loci whose copy numbers are frequently altered in glioblastoma according to our observations (not shown) and previously published data. 4,19 We developed an original endogenous control system and designed specific primer pairs (Supporting Information Table 2) based on the GRCh37/hg19 genome assembly with comprehensive annotations and the data accumulated in the past decade for alterations in copy numbers of genomic regions in glioblastoma.…”
Section: Discussionsupporting
confidence: 59%
“…Loss of heterozygosity (LOH) at markers of the long arm of chromosome 10 is the most frequent (up to 80%) molecular genetic alteration in glioblastoma. 3 Two regions, 10q23-24 and 10q25-pter, are most often affected by LOH. 4 A high LOH frequency is associated with the presence of many tandem and interspersed repeats in the regions.…”
mentioning
confidence: 99%
“…Because we did not observe any improvement in the OS of patients with both MGMT methylation and 10q LOH, we hypothesize that the positive effect of complete MGMT silencing on therapy response can be counterbalanced by the loss of other tumor suppressor genes (e.g. PTEN , ERCC6 and DMBT1 ) mapping to the same region of chromosome 10q and associated with reduced OS (39, 40). …”
Section: Discussionmentioning
confidence: 65%
“…The molecular criteria confirming the primary GB were frequency of EGFR amplification (37.5%), IDH1 mutation (2.44%), and TP53 mutation (26.2%). The results for EGFR amplification, IDH1, and TP53 were partly published before ( Jesionek-Kupnicka et al, 2013).…”
Section: Methodsmentioning
confidence: 99%